2015
DOI: 10.4172/2161-0665.1000228
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Physical Punishment by Teachers and its Associations with Aggression and Victimization at School: A Study among Young Adolescents in Iran

Abstract: Objectives:Physical punishment by teachers is accepted in Iranian schools, but it may at times take extreme forms, such as teachers burning the hands of pupils, or even breaking their bones. The study aims at investigating how frequently such punishments occur, and their relationship to perpetration of and victimization to peer aggression at school. Methods:Data from 1244 young adolescents (649 boys, 595 girls; M age=12.7 yrs, SD=2.1 yrs) was collected in two cities, Mashhad and Eylam, in both public and priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…According to one study, 43% of pupils reported having been physically punished at school (Sheikattari, Stephenson, Assaisi, Eftekhar, & Zamani, 2006). Jaghoory, Björkqvist, and Österman (2015) found that even quite harsh methods of PP at school still occurred in Iran at the time of the study, although exceptionally: 3.8% of the adolescents participating in their study (N = 1,244) had had their hands burnt, and 4.8% reported having had bones broken as a punishment at school. Björkqvist, Österman, and Berg (2011) found that experiences of PP at home were much more frequent (in 39.5% of cases) among victims of school bullying than among non-victims (16.8% of cases).…”
Section: Introductionmentioning
confidence: 95%
“…According to one study, 43% of pupils reported having been physically punished at school (Sheikattari, Stephenson, Assaisi, Eftekhar, & Zamani, 2006). Jaghoory, Björkqvist, and Österman (2015) found that even quite harsh methods of PP at school still occurred in Iran at the time of the study, although exceptionally: 3.8% of the adolescents participating in their study (N = 1,244) had had their hands burnt, and 4.8% reported having had bones broken as a punishment at school. Björkqvist, Österman, and Berg (2011) found that experiences of PP at home were much more frequent (in 39.5% of cases) among victims of school bullying than among non-victims (16.8% of cases).…”
Section: Introductionmentioning
confidence: 95%
“…✓ No matter the context, the age, or the type of aggression, there was an inverse relationship between emotional intelligence and aggressive behavior (García-Sancho et al, 2014;Siddiqui et al, 2022). ✓ There has been strong evidence to suggest that frustration is one of the driving forces behind perversion (Jaghoory, 2018;Tam & Taki, 2007;Vranjes et al, 2021). ✓ Teaching stress management and problem-solving skills can be helpful in combating antisocial behaviors (Kang et al, 2019;Maryam & Ijaz, 2019;Méndez et al, 2019) ✓ Educators believe that the severity of sanctions for bullying behavior serves as an effective deterrent (Roberge, 2012).…”
mentioning
confidence: 99%